PENGARUH METODE KANGOROO MOTHER CARE (KMC) TERHADAP KENAIKAN BERAT BADAN PADA BAYI BARU LAHIR RENDAH (BBLR) - Nur Ajira, Winda; Aidina, Dyka; Darma, Abdi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
The condition of newborn weight and gestational age will affect the infant mortality rate. Newborn babies with a weight less than normal regardless of gestational age are called LBW babies. In Low Birth Weight Babies (LBW), the initiation of bonding attachment between mother and baby is delayed. There needs to be a treatment that can be an alternative solution in the care of low birth weight babies (LBW), one of which is by implementing the Kangaroo Mother Care (KMC) method. This study aims to determine the effect of the Kangaroo Mother Care (KMC) method on weight gain in Low Birth Weight Babies (LBW). This research method is a quasi experiment with a one group pre-test and post-test design. This research was conducted at the Muhammad Sani Karimun Hospital, the sample in this study were 16 LBW babies born in June 2024. The results of this study showed an increase in the average weight of infants after KMC treatment, where the average weight of infants before KMC was 1431 grams, and the average weight of infants after KMC was 1590.63 grams (the difference is 159.63 grams), with a p-value of 0.000 (p <0.05) it can be concluded that there is an effect of the Kangaroo Mother Care (KMC) method on weight gain in LBW. It is expected that mothers can provide KMC method care to increase infant weight, especially in LBW babies. Keywords : Kangoroo Mother Care, Baby, low birth weight babies